What Determines Entrepreneurial Outcomes in Emerging Markets? The Role of Initial Conditions - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (Review of Financial Studies, 2017)
We study how institutions influence start-up characteristics of firms and how these characteristics predict entrants’ growth trajectories over the early firm life cycle. Using census data from India, we find that greater financial development is associated with higher entry rates and smaller-sized entrants. Following entry, however, large and small entrants grow at the same rates across states with different institutions or industries with differing reliance on external finance. The impact of access to finance is greater on start-up size and entry rates than on the subsequent growth of firms during the early life cycle.Received April 30, 2015; editorial decision August 5, 2016 by Editor Andrew Karolyi.